2023
DOI: 10.1002/chem.202300705
|View full text |Cite
|
Sign up to set email alerts
|

A Cytoplasm‐Specific Fluorescent Ligand for Selective Imaging of RNA G‐Quadruplexes in Live Cancer Cells

Abstract: The development of site‐specific, target‐selective and biocompatible small molecule ligands as a fluorescent tool for real‐time study of cellular functions of RNA G‐quadruplexes (G4s), which are associated with human cancers, is of significance in cancer biology. We report a fluorescent ligand that is a cytoplasm‐specific and RNA G4‐selective fluorescent biosensor in live HeLa cells. The in vitro results show that the ligand is highly selective targeting RNA G4s including VEGF, NRAS, BCL2 and TERRA. These G4s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…This preferential colocalization of TOR-G4 with RNA makes the molecule one of a limited number of probes well suited for studying G4 RNA within cells using fluorescence microscopy. 4144…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This preferential colocalization of TOR-G4 with RNA makes the molecule one of a limited number of probes well suited for studying G4 RNA within cells using fluorescence microscopy. 4144…”
Section: Resultsmentioning
confidence: 99%
“…58 In comparison, visualization of RNA G4s (rG4s) is still a relatively new area of study. 4144 Previously, it was suggested that RNA G4s may even be globally unfolded within cells due to the persistent activity of G4 helicases. 59 However, more recent studies have provided extensive evidence that rG4s not only exist within cells but may be pivotal for mediating RNA interactions with proteins that control processes such as splicing, translation and stress granule formation.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of molecular scaffolds was achieved via a rigid but rotatable ethylene bridge. The two π-conjugated scaffolds may form a coplanar structure upon interaction with targeted G4s and then the adduct can generate intensive fluorescence for real-time imaging and monitoring G4s in living cells . To the best of our knowledge, there are no such small-sized, dicationic, mitochondria-selective and G4-targeting ligands reported.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the absence of RNA, the probe binds to DNA, in turn becoming a nuclear stain. This preferential colocalization of TOR-G4 with RNA makes the molecule one of a limited number of probes well suited for studying G4 RNA within cells using fluorescence microscopy. …”
Section: Resultsmentioning
confidence: 99%
“…Historically, quadruplex research has been focused on DNA G4s, which is reflected in the greater availability of fluorescent probes that exhibit nuclear staining . In comparison, visualization of RNA G4s (rG4s) is still a relatively new area of study. Previously, it was suggested that RNA G4s may even be globally unfolded within cells due to the persistent activity of G4 helicases . However, more recent studies have provided extensive evidence that rG4s not only exist within cells but may be pivotal for mediating RNA interactions with proteins that control processes such as splicing, translation, and stress granule formation. …”
Section: Discussionmentioning
confidence: 99%